Study on Presence of Borrelia persica in Soft Ticks in Western Iran - A Barmaki; J Rafinejad; H Vatandoost; Z Telmadarraiy; F Mohtarami; SH Leghaei; MA Oshaghi (Tehran University of Medical Sciences, 2010)
Background: A molecular survey was conducted to investigatethe presence of pathogenic Borrelia persica species causing the tick borne relapsing fever (TBRF) in Takistan district Qazvin Province, western Iran. Methods: A number of 1021 soft ticks were collected from 31 villages including previously reported infected and none-infected TBRF cases and individually examined for the presenceof B. persica DNA by conventional PCR targeting the 16SrRNA. Results: A total of 1021 soft ticks of three species of Ornithodouros tholozani (120: 11.75%), O. lahorensis (461: 45.15%) and Argas persicus (440: 43.1%) were collected and tested against Borrelia infection. Soft ticks were more prevalent (67%) in infected areas than none infected areas. The rate O. tholozani in infected areas was much greater (29 times) than none infected areas. Ninety seven percent of soft ticks in none infected areas were of O. tholozani. Sixteen (16.7%) ticks of tested (n=95) O. tholozani were infected with B. persica. Three (1.3%) out of 205 soft ticks of O. lahorensis were positive for Borrelia sp., and no infection was observed in A. persicus. TaqI RFLP analysisand sequence analysis of the positive PCR products showed the presence of B. persica. The RFLP analysis showed that the positive ticks of O. lahorensis were infected with unknown Borrelia species. Conclusion: This study showed that although there were no TBRF cases in Takisan, but still infected O. tholozani, the known vector of TBRF, presented in the region. Control measures needs to be fulfilled in Thakisan.